Neuroimaging hippocampal subfields in schizophrenia and bipolar disorder: A systematic review and meta-analysis - Haukvik, Unn K.; Tamnes, Christian K.; Söderman, Erik; Agartz, Ingrid (Journal of psychiatric research, 2018)
The hippocampus is a complex structure consisting of subregions with specialized cytoarchitecture and functions. Magnetic resonance imaging (MRI) studies in psychotic disorders show hippocampal subfield abnormalities, but affected regions differ between studies. We here present an overview of hippocampal anatomy and function relevant to psychosis, and the first systematic review and meta-analysis of MRI studies of hippocampal subfield morphology in schizophrenia and bipolar disorder. Twenty-one MRI studies assessing hippocampal subfield volumes or shape in schizophrenia or bipolar disorder were included (n 15–887 subjects). Nine volumetric group comparison studies (total n = 2593) were included in random effects meta-analyses of group differences. The review showed mixed results, with volume reductions reported in most subfields in schizophrenia and bipolar disorder. Volumetric studies using ex-vivo based image analysis templates corresponded best with the shape studies, with CA1 as the most affected region. The meta-analyses showed volume reductions in all subfields in schizophrenia and bipolar disorder compared to healthy controls (all p < .005; schizophrenia: d = 0.28-0.49, bipolar disorder: d = 0.20-0.35), and smaller left CA2/3 and right subiculum in schizophrenia than bipolar disorder. In conclusion, the hippocampal subfields appear to be differently affected in psychotic disorders. However, due to the lack of control for putative confounders such as medication, alcohol and illicit substance use, and illness stage, the results from the meta-analysis should be interpreted with caution. Methodological subfield segmentation weaknesses should be addressed in future studies. [Display omitted] •Review (21 MRI-studies): widespread volume reductions and shape alterations.•Changes were in part related to clinical symptoms and lithium use.•Meta-analysis (8 studies): larger reductions in schizophrenia than bipolar disorder.•Methodological differences may confound the results.•Future studies using newer protocols in larger subject samples are warranted.